The Bourne ultimatum - Ludlum, Robert, 1927- (New York : Random House, 1990)
A mild-mannered professor is forced to assume again the deadly alter ego he created in Vietnam years ago as part of the Medusa Brigade.
Booklist.
Wilson's Fiction.
Wilson's Senior High School.
Adult.
Adult
Keywords: Assassins -- Fiction; Assassins -- Fiction